2009
DOI: 10.1093/rpd/ncp234
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of personal exposure to UV radiation of workers and general public

Abstract: Due to meteorological conditions variability and to the variability of exposure patterns, which can be largely different during a working day, personal dosemeters use can be necessary to obtain a correct quantitative evaluation of the radiation dose absorbed by an exposed worker. Different classes of personal dosemeters exist and, among them, electronic dosemeters and polysulphone film dosemeters. An experimental campaign is presented conduced in a cultivated area of Tuscany and some aspects are discussed abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, during the measurement campaign in the fishermen group, performed according to a preventive purpose [25,27], we could not be able to interview the workers with our ad hoc questionnaire: this factor is a relevant limitation for the current development of our methodology because at present we can't associate the questionnaire's answers to specific individual measurements. Despite this limit, the occupational exposures suggested by our questionnaire or measured in the group of fishermen are in accordance with recent studies that have shown an exposure in terms of Standard Erythemal Dose (SED) of 9.9 SED in Australia [13], 11.9-28.6 SED in Switzerland [14], 6.11 SED in Spain [15] for the construction sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the measurement campaign in the fishermen group, performed according to a preventive purpose [25,27], we could not be able to interview the workers with our ad hoc questionnaire: this factor is a relevant limitation for the current development of our methodology because at present we can't associate the questionnaire's answers to specific individual measurements. Despite this limit, the occupational exposures suggested by our questionnaire or measured in the group of fishermen are in accordance with recent studies that have shown an exposure in terms of Standard Erythemal Dose (SED) of 9.9 SED in Australia [13], 11.9-28.6 SED in Switzerland [14], 6.11 SED in Spain [15] for the construction sector.…”
Section: Discussionmentioning
confidence: 99%
“…The highest exposure to solar UVR has been measured for the nose, ear and the upper part of the fishermen's shoulders with the electronic dosimeter placed on the cap's peak of the outdoor workers, reaching an effective radiant energy of 0.9 kJ/m 2 . The lowest measure of 0.04 kJ/m 2 was collected on the third boat (for further details on the measurements performed and on the characteristics of the fishermen, see also the paper published by 2 of the authors [27]). …”
Section: Individual Exposure Datamentioning
confidence: 99%
“…Exposure studies and sun prevention campaigns have focused mainly on situations of obviously high exposure such as outdoor sport, beach and tourism in high UV risk countries (mainly Mediterranean countries, South America, Australia and Africa) 8–13 . A few UV exposure and prevention campaigns have also focused on every day life activities including school children, workers, of ‘typical lifestyle behaviours’ 14–17 . To our knowledge no study evaluated UV exposure during cultural tourism.…”
Section: Introductionmentioning
confidence: 99%
“…The first aim of our study was to assess the UV exposure of vineyard workers at a rural site in Tuscany, Italy using UV sensitive polysulphone (PS) badges during different stages of their occupational activity. The study was stimulated by the Italian Institute for Occupational Prevention and Safety (ISPESL) and the Section of Occupational Medicine Department of the University of Siena, within the framework of a survey on free radicals as markers of oxidative stress following UV exposure, in outdoor and indoor workers (29).…”
Section: Introductionmentioning
confidence: 99%